The Development and Effectiveness of Non-face-to-face Self-regulation Training Program for Student-athletes - Hae-ju Park (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study was to develop a non-face-to-face self-regulation training program for middle and high school student-athletes through the conduct of a group online video counseling session, as well as to verify the effectiveness of such a tool. METHODS Based on the models of Zimmerman(2000) and Han Si-wan (2008), the 12-session non-face-to-face self-regulation training program consisting of interactions involving cognitive, emotional, and behavioral factors was developed and used on a 16-member experimental group. Additionally, self-regulation and mental toughness questionnaires were given to each member before and after the program, and the results were compared with the results of a 17-member control group. Since a qualitative evaluation was conducted, recorded training contents were organized into a text file; after which, a step-by-step coding procedure was performed, and then meanings and themes were identified and categorized. RESULTS Quantitative analysis found that the volitional inhibition mode of the control group decreased significantly; this was in comparison to the increase in the self-regulation mode of the experimental group. In addition, among the seven sub-factors of the mental strength test of the experimental group, a significant increase was found in the post-test of self-belief, attention control, emotional regulation, resilience, and optimism factors. As a result of qualitative data analysis, they complained of difficulties in the early stages of participation, but gradually recognized their problems and searched for changes, showed changes in cognition, emotion, and behavior as they approached the end of the study period. CONCLUSIONS It can be said that the non-face-to-face self-regulation training program helped student athletes improve their school life and performance by driving positive cognitive, emotional, and behavioral changes.